1985
DOI: 10.1007/bf00265023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insulin receptors on heterogeneous eukaryotic cell populations with fluorochrome-conjugated insulin and fluorescence-activated cell sorter. Advantages and limitations to the 125I-labelled insulin methodology

Abstract: The diversity in insulin receptor expression within eukaryotic cell populations can be studied with fluorochrome conjugated reagents with high affinity to the insulin receptor in combination with flow cytometry. We studied the optimal conditions for application of fluorescein isothiocyanate (FITC) conjugated insulin in combination with the fluorescence activated cell sorter (FACS) to analyse insulin receptor expression, and also studied the feasibility of this method for identifying and isolating viable subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…One could therefore assume that the reaction of BITC with exposed surface amino acid residues was not involved in substrate catalysis. Although it has been shown that the modification of rabbit P450 2B4 by fluorescein isothiocyanate caused a 25% loss in benzphetamine N-demethylation activity due to modification of the ε-amino group of lysine-382 (), the result described in this study is similar to other reports where enzyme activity was not affected even though enzyme modification clearly occurred ( , ).…”
Section: Discussionsupporting
confidence: 88%
“…One could therefore assume that the reaction of BITC with exposed surface amino acid residues was not involved in substrate catalysis. Although it has been shown that the modification of rabbit P450 2B4 by fluorescein isothiocyanate caused a 25% loss in benzphetamine N-demethylation activity due to modification of the ε-amino group of lysine-382 (), the result described in this study is similar to other reports where enzyme activity was not affected even though enzyme modification clearly occurred ( , ).…”
Section: Discussionsupporting
confidence: 88%
“…F-insulin was synthesized according to the previous reported procedure. 38 The nanoparticles were characterized for particle size and zeta potential with a Malvern Zetasize NanoZS90 (Malvern Instruments Ltd., U.K.). The morphology of NCs/NPs was examined by transmission electron microscope (TEM, H-600, Hitachi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, fluorescent-labeled nanoparticles were prepared with the same method using FITC-labeled insulin (F-insulin). F-insulin was synthesized according to the previous reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent labeled nanocomplexes were also prepared with the same method using FITC-labeled insulin (F-insulin). F-insulin was synthesized according to the previous report …”
Section: Methodsmentioning
confidence: 99%
“…F-insulin was synthesized according to the previous report. 17 The prepared nanocomplexes were characterized for particle size and zeta potential with a Malvern Zetasize NanoZS90 (Malvern Instruments Ltd., UK). All measurements were performed in triplicate.…”
Section: ■ Introductionmentioning
confidence: 99%